Redefining existing functionality of the regulatory portal for immediate access to outputs of employees - Coronel, Aira Juana M.
The employees' knowledge is considered as one of the most important sources of a business's competitive advantage. In this regard, companies are beginning to execute plans and implementing methods of keeping said knowledge.